IMPLEMENTASI TEORI HUKUM ROSCOE POUND DALAM PEMBANGUNAN HUKUM DI INDONESIA (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
This research discusses the application of Roscoe Pound's Legal Theory in the context of legal development in Indonesia. This type of research is normative legal research with a literature and legal study approach. The data used includes primary data in the form of legal literature and secondary data consisting of primary, secondary and tertiary legal materials. The data collection method was carried out through document study and literature study, while the data analysis method used a qualitative descriptive approach. The research results show that: first, the principles of Roscoe Pound's Legal Theory can help make legal development in Indonesia more responsive to community needs, support social justice, and encourage positive change in various areas of life. Second, the effectiveness of applying Roscoe Pound's Legal Theory in supporting the goals of legal development in Indonesia can be seen from its role as a tool of social control, Social Engineering and balancing interests. A comprehensive evaluation requires analysis of empirical data, case studies, and community satisfaction surveys to provide a clearer picture of the successes and challenges in applying this theory.